PENGELOLAAN ARSIP VITAL RENCANA KERJA DI SEKRETARIAT UMUM KEPOLISIAN DAERAH ISTIMEWA YOGYAKARTA - , LINA SAKINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report was conducted to determine and increase knowledge about the protection and safeguarding of vital records. The purpose of the final report is to explore theory of the vital records management. Moreover, it can also be compared to the theory learned in lecture with the state of the field. Most of this final report discusses started from the identification process and the managing of work plan vital records. The process of vital records starting from the condition and location of records, records storage infrastructure, the protection and security of vital records, control and monitoring of vital records and records access. As for the method of data collecting on vital records management used to complete the final report comprises observation, interview, and study of library. The observation method is direct observation the processing of vital records Renja Sekretariat Umum Kepolisian Daerah Istimewa Yogyakarta and interview methods. This method is used to obtain data from informants who are competent at the field in the protection and safeguarding of vital records. Written sources method as references or obtain data to compare of library materials in study of library with the theory and direct practice in field. The conclusion of this final report, the management of vital records Renja Sekretariat Umum Kepolisian Daerah Istimewa Yogyakarta should be optimalize. On additionally archivists who at Sekretariat Umum Kepolisian Daerah Istimewa Yogyakarta havenât enough knowledge in processing vital records, especially for the renja. This is evident from the lack of uniformity in the provision of access vital. Unavailability of records storage of vital infrastructure is inadequate and barriers to the storage implementation of the vital records Renja Sekretariat Umum Kepolisian Daerah Istimewa Yogyakarta.